Sorption of Copper Metal Solution by Wetland Soil - Edwayne Liew, Joshua; Khai Wong, Jee; Fai Chow, Ming; Chiet Chai, Voon (International Journal of Engineering and Technology, 2018)
This study is to determine the equilibrium time and removal efficiency of copper by wetland soil. The wetland is located near the car park at College of Engineering, UNITEN. Wetland soil were collected randomly at a depth of 20 cm to 50 cm. Soil samples are then oven dried at 105 oC for 48 hours. After that it is let to cool down for 15 minutes before crushed and sieved through a 2.36 mm size sieve pan. Based on the Batch equilibrium method, the wetland soil is soaked in copper metal solution for different study time of 1, 2, 3, 5, 24, 168 and 336 hours. Each studied time are prepared in three samples, with initial copper metal solution concentration 1 mg/l. Parallel method is used in order to prevent disruption on the soil to solution ratio. Results obtained show that the concentration of copper metal solution decreases gradually and reached a constant during the period of 24 hours to 168 hours. Desorption phenomenon also occurred during that period of time. The removal percentage shows an increase up to 50 %. It clearly shows that adsorption of copper metal solution by wetland soil is effective.Â
Keywords: Copper metal solution removal; Heavy metal sorption; Wetland soil